Metachromatic leukodystrophy associated with choledochal cysts and gallbladder papillomatosis - Raed Al-Taher; Fareed Khdair Ahmad; Mohammad Rashdan; Ibrahim Khrais; Sahar Almustafa (Elsevier, 2019)
Metachromatic Leukodystrophy (MLD) is an autosomal recessive lysosomal storage disease caused by the deficiency of the enzyme arylsulfatase A which is responsible for the desulfation of cerebroside sulfate, a myelin glycolipid. Accumulation of these sulfatides in the macrophages of various tissues causes a wide spectrum of presentations including central and peripheral nervous system dysfunction and gallbladder abnormalities. We report a case of a 6-year old girl with infantile Metachromatic Leukodystrophy who was found to have elevated liver enzymes, biliary markers and total and direct bilirubin during work-up for unexplained high-grade fever. Imaging showed dilated intra and extra hepatic biliary tree, markedly expanded CBD by dense content and multiple variable sized filling defects with narrowing in between. The dense content was confirmed to be mucosal papillomatosis with hyperplastic epithelium. To the authors' knowledge, obstructive extra-hepatic biliary tree polypoid masses and cystic dilation with metachromatic leukodystrophy have not previously been reported. Keywords: Metachromatic leukodystrophy, Gallbladder papillomatosis, Choledochal cysts